ANALISIS LAYANAN UNGGULAN ENHANCED RECOVERY AFTER CAESAREAN SURGERY (ERACS) DI RUMAH SAKIT MUHAMMADIYAH LAMONGAN - Muhtaromah; Imanda Dyah R; Neneng Huriyah (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
The Enhanced Recovery After Caesarean Surgery (ERACS) method in several studies has been proven to accelerate patient recovery. Muhammadiyah Lamongan Hospital began implementing the ERACS method as one of the leading services since 2022. This study aims to analyze ERACS services from a review of effectiveness, time of recovery, and patient satisfaction. This study was descriptive analytic and retrospective cohort, using questionnaire instruments. The research took place at Muhammadiyah Lamongan Hospital, in the period 01 August 2022 to 31 July 2023. The data was processed descriptively and Pearson Chi-square analysis. A total of 120 respondents met the inclusion criteria, with an average age of 29.98 (±4.63) years. Most of patients (70.83%) had a pain scale of 2 or mild pain, and as many as 20% of patients felt no pain after surgery. Most patients (54.17%) said they could walk 6 hours after surgery, and 4.17% of patients started walking 2 hours after surgery. As many as 75.83% of patients did not feel complaints or side effects after surgery, and only 24.17% of patients felt complaints with symptoms of dizziness, nausea/ vomiting, and chills. There are two alternative combinations of per-oral analgesics, i.e Mefinal-Farmadol and Mefinal-Ulcetra. When compared to the effectiveness between the two drug groups, Pearson chi-square analysis showed no significant difference between the two regimen groups (p 0.742). In the aspect of service satisfaction, most of respondents (99.17%) expressed satisfaction with ERACS services at Muhammadiyah Lamongan Hospital.